2009
DOI: 10.1111/j.1467-8578.2009.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

FOCUS ON PRACTICE: Inclusion and museums: developing inclusive practice

Abstract: Recent policy on inclusion has had an impact on the development of museum galleries and related educational provision. Museums are used as learning organisations and, as such, need to consider how to create an inclusive environment. However, inclusive provision for people with learning difficulties in museums tends to be isolated and small scale, lacking the formal structure found within schools. While much can be learnt from the development and evaluation of practice in schools, there is little research or pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
(5 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, access is undoubtedly the necessary condition, but it is not identical to active involvement and engagement or to social inclusion (DCMS, 2000;Rappolt-Schlichtmann & Daley, 2013;Spandagou, 2011). In order to respond to the heterogeneity of persons with disabilities and the diverse needs and characteristics of different persons -including children and school groups of children with and without disabilities -it seems that the principles of the theoretical approaches of Differentiated Instruction (DI) and Universal Design for Learning (UDL) are the most appropriate both in formal and nonformal learning environments including museums (Fletcher, 2013;Rappolt-Schlichtmann & Daley, 2013;Shepherd, 2009).…”
Section: Schools-museums Relationship and The Benefits For Children With Disabilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, access is undoubtedly the necessary condition, but it is not identical to active involvement and engagement or to social inclusion (DCMS, 2000;Rappolt-Schlichtmann & Daley, 2013;Spandagou, 2011). In order to respond to the heterogeneity of persons with disabilities and the diverse needs and characteristics of different persons -including children and school groups of children with and without disabilities -it seems that the principles of the theoretical approaches of Differentiated Instruction (DI) and Universal Design for Learning (UDL) are the most appropriate both in formal and nonformal learning environments including museums (Fletcher, 2013;Rappolt-Schlichtmann & Daley, 2013;Shepherd, 2009).…”
Section: Schools-museums Relationship and The Benefits For Children With Disabilitiesmentioning
confidence: 99%
“…Although the aforementioned principles of DI and UDL concern formal education, in the field of nonformal learning environments (e.g. museums), these principles are considered as the most appropriate in order to respond to the diverse needs and characteristics of different persons as well as to the heterogeneity of persons with disabilities (Argyropoulos & Kanari, 2019;Fletcher, 2013;Nikolaraizi, Kanari & Marschark, 2020;Rappolt-Schlichtmann & Daley, 2013;Shepherd, 2009). As Shepherd (2009) asserts, museum professionals can learn and benefit from the principles of DI in order to design inclusive and meaningful learning experiences for children with diverse needs and characteristics.…”
Section: Differentiated Instruction and Universal Design For Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Haworth and Williams (2012) describe how they used iPads or smartphones to enable people with intellectual impairments to follow trails in a museum by scanning QR codes. Shephard (2009) argued that while the MLA framework provides a starting point for developing an inclusive learning environment, without expert knowledge (e.g. of intellectual impairments) museum staff may struggle to implement successful methods.…”
Section: Approaches To Inclusion and Participation For Museum Visitors With Intellectual Impairmentsmentioning
confidence: 99%
“…The development of learning and teaching mediated primarily through language was focused on four teaching and learning strategies: 1) the DL being a passive recipient of language through exhibitions, where the social message produced by the designers was preeminent [26]; 2) the development of higher language and social skills [12] [13]; 3) teaching the contents of objects that are thought to be unperceivable through other means, such as painting to viewers with visual impairments, or articles where touch was prohibited [10] [11]; and 4) the interaction with virtual museums that can't be visited in person [14]. Furthermore, it was observed that articles focussed on direct sensory experience to develop discussions on teaching and learning through three different strategies: 1) the development of understanding through the stimulation of senses, where one sense was impaired [17] [25]; and 3) where it was felt that learning through language was impaired, the sensory experience of exhibits was designed to provide at least a partial substitution [23] [24].…”
Section: Ep3: Learning Focusing On Perceptions Versus Learning Througmentioning
confidence: 99%